A disaggregated analysis of public spending and economic growth in developing and high-income countries - Jarupasin, Kritchasorn (Thammasat Review of Economic and Social Policy, 2019)
In this study, the permanent growth effects of fiscal policy are investigated across countries with different income levels using the public-policy endogenous growth model, where public spending is classified by function. The endogeneity problems associated with taxes and investment are taken into account, as is a possible non-linear relationship between government expenditure and economic growth. The results have shown that gross capital formation is the only control variable that has a significant positive coefficient in all growth regressions, while the evidence of conditional convergence hypothesis is reaffirmed. An increase in transportation and communication spending is conducive to growth in both developing and high-income countries, whereas other types of spending are not.